The Dynamics of Adversity Quotient of Vocational School Student from Broken Homes in Career Planning - aniza putri, novanda; Basuki, Agus (Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract: The changing family structure in Indonesia with the increasing number of broken homes has an impact on the lives and futures of adolescents, including in determining their career paths. This study aims to describe the Adversity Quotients of students from broken homes in facing pressure, the support they receive, and how they survive and move forward. The research was conducted at a vocational school in Nanggulan District using a qualitative approach and phenomenological method. Data was collected through in-depth interviews, observation, and documentation. The results of the study show that for students from broken homes, Adversity Quotient means trying to get back up, staying motivated to go to school, and not giving up even without the support of a complete family. They are driven by a desire for independence, a sense of responsibility, and a drive to change their fate. Support from teachers, friends, and extended family provides additional strength. The strategies used include focusing on completing school, seeking work experience, and taking steps towards independence.